Prognostic impact of KIHON checklist score in elderly patients with hemodialysis initiation - Hayato Fujioka; Tsutomu Koike; Teruhiko Imamura; Shingo Yokoyama; Sayaka Murai; Kota Kakeshita; Hidenori Yamazaki; Koichiro Kinugawa (Renal Replacement Therapy, 2024)
Abstract Background Frailty pervades the demographic of individuals afflicted by chronic kidney disease (CKD) and exhibits a robust correlation with a less favorable prognosis. Nonetheless, the evaluation and prognostication of frailty within the incipient stages of dialysis initiation remain shrouded in ambiguity. The necessity arises for an uncomplicated metric that holistically assesses frailty among aged CKD patients, one which lends itself to pragmatic clinical application. Methods In our prospective endeavor, we conducted assessments using the “KIHON checklist (KCL),” a questionnaire comprising 25 points, thoughtfully crafted by the Japanese Ministry of Health, Labour and Welfare to provide a thorough evaluation of the elderly population. This assessment was administered at the commencement of hemodialysis in patients aged 65 years or older. Subsequently, we analyzed the prognostic ramifications of the initial KCL scores on the composite primary endpoint, which encompassed the undesirable outcomes of either being bedridden or succumbing to mortality. Results A total of 24 patients (median age 76 years, 20 men) were included. The median KCL score was 6 [4, 10] points, and it was significantly correlated with the number of components in the revised Japanese Cardiovascular Health Study, which is a diagnostic criterion for frailty (p < 0.05). The group with a KCL score ≥ 10 points had a significantly lower 1-year freedom from the primary endpoints than the other group (43% versus 87%, p < 0.05). Among the components of the KCL, physical strength was significantly associated with the prognosis (p < 0.05). Conclusion The screening protocol employing the KCL during the commencement of hemodialysis among elderly individuals proved to be a valuable tool for the anticipation of both the state of being bedridden and mortality.